Development and Testing the Effectiveness of Teacher Training Models in Forming Islamic Character - Syamsudin Syamsudin; Ahmad Tafsir; H.E. Mujahidin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
In this era, all parties, especially the government, focus on building children's character. The importance of the role of individuals who have good morals will be very important for national development so that it will give birth to a young generation with character who upholds moral principles with good morals. Therefore, character building is often used as an indicator of the success of a nation itself. This research is expected to be able to develop a teacher coaching model, especially elementary school teachers in shaping Islamic character. The purpose of this study was to determine the teacher's ability to understand Islamic character. Another objective of this research is to analyze the need for forming Islamic character, to analyze the suitability of the tools developed, and to analyze the effectiveness of the training model in increasing teachers' understanding of Islamic character. This study found that Islamic class design is considered important in shaping Islamic character, besides that there are 10 indicators of Islamic character that must be instilled in students. The results of other studies are that the Islamic character training model is feasible to use and the Islamic character training model is effective in increasing teacher understanding of Islamic character.